Support from Family , Health Worker and Elderly Hypertension Health Care Access In Controlling health - Edy Susanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. The aim of this study is to determine the relationship between the support from family, health worker and Elderly Hypertension Health Care Access and the practice of patient health controll in Kangkung Village, Demak by using cross sectional study approach. The number of samples was 285 respondents. The results shows that there is a relationship between the support from family, health worker and Elderly Hypertension Health Care Access and the practice of patient health control. High social support will make the elderly live more optimistically, more skilled in completing the needs of psychology, having a higher system, having lower anxiety, having higher interpersonal skills, and have ability to adapt to stress so that he is able to face and to solve his health problem and is able to perform optimally in his own health control. Access to health services has an important role in the effort of elderly hypertensive practices in controlling their health, the better access to health services, the better the health control practices.